Investigation and Study of Vital Factors in Selection, Implementation and Satisfaction of ERP in Small and Medium Scale Industries - Kanchana V; Sri Ranjini S (Institute of Advanced Engineering and Science, 2018)
Small and Medium Scale Enterprises in India are the most productive job designers and forerunners in developing new ideas in the field of business. SMEs not only play a vital role in providing large scale employment openings at reasonably lower capital than large businesses but also help in industrialization of rural areas in India. SMEs are complementary to large industries as subsidiary units and this sector contributes immensely to the socio-economic development of the country. Small and Medium scale industries have grown tremendously in the last 5 decades. In spite of high enthusiasm and intrinsic capabilities to grow, there are a number of problems faced by SME‟s; one of them is the „technological obsolescence‟. The SME sector in order to outcome this challenge must make advances in the field of engineering and technology. Adoption of Information Communication Technology in their business process can enhance their productivity and global competency.in the market. In this connection Enterprise Resource Planning plays a vital role in the SME‟s business process strategy. Hence there is a need for the motivation to implement ERP and find whether the current ICT solution the industries using are adequate for their strategy. In this paper we try to find out which ERP vendors does the SME sectors prefer, are the features of the ERP system and the implementation methodology selected have met the business goals and user satisfaction.